PERBANDINGAN APLIKASI SMART CONTINUITY OF CARE BERBASIS ANDROID (MONSCA) DENGAN BUKU KIA TERHADAP PENINGKATAN PENGETAHUAN IBU HAMIL DALAM PENANGANAN FAKTOR RISIKO KEHAMILAN - -, Hikmawati; Werna Nontji; Syafruddin Syarif (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103)
Quality and ongoing antenatal care is considered effective in reducing complications during pregnancy. It's important to maintain a healthy pregnancy, improve pregnancy outcomes by identifying complications, promoting healthy behavior and giving clients the opportunity to be actively involved with health care providers. This study aims to determine differences in knowledge of pregnant women about handling risk factors for pregnancy before and after the Android-based Smart Continuity of Care (MONSCA) application and before and after conventional methods (the MCH handbook) are given. The research was carried out in the Tanete Health Center and the Bontobangun Health Center in Bulukumba Regency. The method used is an experimental quasi-experimental type of research (pretest-posttes only control design). In this study, a sample of 18 pregnant women was divided into two groups (9 intervention groups and 9 control groups). The sampling technique uses purposive sampling. Data were analyzed by different test by looking at normality and Wilcoxon test to see differences in knowledge. The results showed there were differences in the knowledge of pregnant women regarding the handling of pregnancy risk factors before and after the MCH handbook was given with a value of p = 0.024 (p <0.05), it appeared that pregnant women had increased knowledge but there were also pregnant women whose knowledge remained. And there is a difference in the knowledge of pregnant women regarding the handling of pregnancy risk factors before and after the MONSCA application is given with a value of p = 0.007 (p <0.05), it appears that all pregnant women have increased knowledge after being given the MONSCA application. The conclusion of increasing knowledge of pregnant women before and after the Android-based Smart Continuity of Care (MONSCA) application is better than the MCH book. It is hoped that this research can be developed in web-based childbirth childbirth care.